The Influence of Cognitive Conflict Strategies on Students' Mastery of Computational Thinking-Based Mathematical Concepts - Rusmini Rusmini; Muhammad Rizky Mazaly (Sean Institute, 2023)
Cognitive conflict is a condition where students encounter new experiences that are not neatly arranged in their cognitive structure. The process of assimilation between old and new concepts in students' cognition. So to hone and improve students' cognitive abilities, it is necessary to have repetition aimed at training students' computational thinking skills which will affect their mathematical mastery. The purpose of this study was to see the effect of cognitive conflict on students' mastery of mathematical concepts. The research method is a case study with a qualitative descriptive and quantitative approach. Learning was carried out to 35 semester II students collaboratively in mastering integral concepts. Pretests are given to determine initial mathematical abilities, then problems are given and solved with computational thinking-based cognitive conflict strategies. The results obtained were very significant for moderate initial abilities, but for high initial abilities it did not affect it, for low initial abilities there was no response. The process that occurs during settlement is very conducive. Post-test results compared to pre-test there is a significant difference